Multiband antenna for mobile handset - Ahmed, Syed Faiz (2005)
Modern cellular phone systems currently operate at a number of frequency bands, the most common being 900MHz, 1.8GHz and 2.0GHz. As mobile phones are becoming smaller it is not feasible to simply equip the handset with an array of antennas, each tuned for a specific frequency band. This has resulted in a demand for antennas that can operate at multiple bands without the need for multiple antennas. The Inverted-F Antenna (IFA) has been demonstrated to be capable of operating at multiple frequencies. Another approach dealing with the ever-diminishing space available on handsets is to conform the antenna. This involves wrapping the microstrip antenna around a cylindrical surface. The results of this approach using the IFA are encouraging, especially in terms of space minimization, bandwidth enhancement and return loss reduction. The purpose of this thesis is to design a conformal antenna for a mobile handset. The first step is to choose a suitable planar triple-band antenna capable of operating at 900MHz, 1.8GHz and 2.0GHz. The antenna that is selected for this thesis is the E shaped planar IFA. This antenna should easily be tuned for correct frequency operation and possess a compact design. The design is created by using, an electromagnetic simulation software package. Once the planar version of the antenna will be simulated, the antenna will then made conformal.